2019
DOI: 10.1111/all.13937
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mepolizumab in patients with previous omalizumab treatment failure: Real‐life observation

Abstract: coagulation cascade and of its intensity were not able to predict the clinical response to omalizumab.Our data confirm that the activation of the coagulation cascade represents a marker of CSU severity, 1 as it does not occur in subjects with a mild disease. The lack of an association between baseline plasma D-dimer levels and response to omalizumab suggests that the activation of the coagulation cascade, starting with the hyper-expression of tissue factor by eosinophils and endothelial cells triggering the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
36
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 8 publications
6
36
2
2
Order By: Relevance
“…On the opposite, the impact of MEP on atopic dermatitis was clinically more apparent, despite in our population, the affected patients were only 9 (7%). Finally, it is noteworthy that the 27 patients who previously failed to respond to Omalizumab, had all a significant benefit with MEP, as already described [34]. The occurrence of adverse events was low.…”
Section: Discussionsupporting
confidence: 60%
“…On the opposite, the impact of MEP on atopic dermatitis was clinically more apparent, despite in our population, the affected patients were only 9 (7%). Finally, it is noteworthy that the 27 patients who previously failed to respond to Omalizumab, had all a significant benefit with MEP, as already described [34]. The occurrence of adverse events was low.…”
Section: Discussionsupporting
confidence: 60%
“…In the OSMO study, a multicenter, open-label, single-arm, 32-week trial, patients with severe asthma uncontrolled by omalizumab showed an improvement in asthma control after switching to mepolizumab [75]. Interestingly, this result was confirmed by real-world evidence [76]. Preliminary findings also suggest that that in patients treated with mepolizumab who had poor asthma symptom control, switching to benralizumab led to improved QoL scores and reduced OCS maintenance doses [77].…”
Section: Discussionmentioning
confidence: 88%
“…In the OSMO study, among 145 patients who were switched to mepolizumab, the rate of clinically significant exacerbations during the 32-week study period decreased by 64% compared with the year prior to study enrollment 6 . After 1 year of mepolizumab treatment, Bagnasco et al 7 registered a decrease in the mean exacerbation rate of 81% in their 27 patients. Similarly to what was found by Bagnasco et al, 7 in our 41 patients the reduction in the mean exacerbation rate was 83%.…”
Section: Discussionmentioning
confidence: 93%